The communities of practice in an innovative enterprise. - Leal, Wilson Luiz Martins; Baêta, Adelaide Maria Coello (Journal of Technology Management & Innovation, 2006)
The emergence of the Web has brought proximity and favored partnership among different groups viewing to cooperate in the generation of knowledge and in the process of innovation. Among the organizational forms of cooperation, the communities of practice (COPs) have been notable as a propitious activity for joining work groups aiming at creating and sharing knowledge as well as problem solving (Wenger et al., 2002). For some authors, communities of practice have always been part of the informal structure of any organization. However, IT has made it possible to exchange knowledge and ideas at an unprecedented pace. The aim of this paper is to analyze the formation and performance of communities of practice as a tool for enterprise innovation. The methodology used in this paper is based on a case study of a multinational company whose performance as an innovative enterprise has been outstanding.